The Influence of Kyai Leadership and Institutional Management on Santri Discipline: The Mediating Role of Self-Awareness in an Islamic Boarding School Context - Zainal Mustafidin; Muhammad Thoyib (Universitas Nurul Jadid, 2026)
Discipline is a fundamental component of character formation in Islamic boarding schools (pesantren). However, disciplinary violations among santri persist despite the presence of kyai leadership, the implementation of ta’zir (Islamic disciplinary sanctions), and institutional supervision, indicating that external control mechanisms alone may be insufficient to foster sustainable discipline. This study examines the relationships among Kyai Leadership, Educational Management Performance, Ta’zir, Self-Awareness, and Student Discipline using a quantitative design. Self-Awareness is conceptualized as a psychological internalization mechanism grounded in character education and self-regulation theory. Data were collected from 113 santri through purposive sampling and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The measurement model met established reliability and validity thresholds. The structural model explains 58.40% of the variance in Student Discipline (R² = 0.584), indicating substantial explanatory power. The results show that Kyai Leadership does not have a significant direct effect on Student Discipline (β = 0.023; T = 0.217; p = 0.828), suggesting that charismatic authority alone may no longer serve as a primary predictor of disciplined behavior. In contrast, Educational Management Performance significantly influences Self-Awareness (β = 0.604; T = 4.057; p < 0.001) and Student Discipline (β = 0.318; T = 2.689; p = 0.007). Self-Awareness also significantly affects Student Discipline (β = 0.489; T = 4.429; p < 0.001) and partially mediates the relationship between management performance and discipline (β = 0.296; T = 2.836; p = 0.005). These findings indicate a shift from authority-based discipline toward system-based governance supported by psychological internalization processes and suggest strengthening institutional management alongside students’ self-regulatory development.